PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS SPARKOL VIDEOSCRIBE YANG DIINTEGRASIKAN DENGAN WONDERSHARE FILMORA PADA MATA PELAJARAN GEOGRAFI MATERI MITIGASI BENCANA ALAM - Yunita Bouato; Fitryane Lihawa; Rusiyah Rusiyah (JAMBURA GEO EDUCATION JOURNAL, 2020)
Development of Learning Media based on Sparkol VideoScribe Integrated with Wondershare Filmora on Geography Subject with Material of Natural Disaster Mitigation. This research aims to know the development of learning media based on Sparkol VideoScribe integrated with Wondershare Filmora on geography subject with material of natural disaster mitigation. This research applies Research and Development (R and D) method  developed by Borg and Gall and adapted to the needs of the researcher. Data collection was conducted using observation, interview, questionnaire, and documentation in which the instrument used in the form of assessment criteria to know the feasibility of the media from the material expert, media expert, and geography teachers as well as students' responses on the learning media by using questionnaires. The collected data is research finding regarding the quality of learning media and suggestions for product revisions. The results of the validation of the material expert, media expert and the geography teacher obtained an average rating of 94.90% which is classified into "extremely valid " category. While the students' responses based on the  results of a limited scale trial obtained a value of 89,88%, which is classified into the â€œextremely goodâ€ category. Then the students' responses based on the results of the general scale trial obtained a value of 84,59%, which is classified into the â€œextremely goodâ€ category. Thus, it can be concluded that learning media based on Sparkol VideoScribe integrated with Wondershare Filmora on geography subject with the material of natural disaster mitigation can be used as learning media in school and obtained good responses by students.